The effect of global travel on the spread of SARS - Shigui Ruan; Wendi Wang; Simon A. Levin (Mathematical Biosciences and Engineering)
The goal of this paper is to study the global spread of SARS. Wepropose a multiregional compartmental model using medical geography theory(central place theory) and regarding each outbreak zone (such as Hong Kong,Singapore, Toronto, and Beijing) as one region. We then study the effect ofthe travel of individuals (especially the infected and exposed ones) betweenregions on the global spread of the disease.